MAGNETIC AFTEREFFECT IN NANOCRYSTALLINE FE88ZR7B4CU1 ALLOY - KIM, KY; NOH, TH; LEE, YH; KANG, IK; KANG, T (AMER INST PHYSICS, 1993)
The magnetic relaxation phenomenon was investigated by using the pulse method for an Fe88Zr7B4Cu1 alloy with nanoscale grain structure, which was prepared by melt quenching and a subsequent annealing. In order to know the relationship between the microstructure and the magnitude of magnetic aftereffect in the nanocrystalline state, annealing temperature dependence of volume fractions of crystalline bcc-Fe and residual amorphous phase was also measured. It was found that disaccommodation occurred in this nanocrystalline alloy, and the intensity of disaccommodation decreased as the fraction of the crystalline bcc-Fe phase increased. Moreover, the jumping field, defined by the magnetic field, at which initial magnetization curve rises abruptly decreased as the fraction of residual amorphous phase was reduced. From the observed results, the magnetic aftereffect was considered to result from the residual amorphous phase.
Keywords: GRAIN-STRUCTURE; CRYSTALLIZATION